Evaluating User Interface and User Experience in Digital Philanthropy Platform: A Study of Kitabisa.com - I Wayan Surya; Ramanda Dimas Surya Dinata; Ari Rimbawan (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
The rapid growth of digital philanthropy in Indonesia has encouraged the development of social crowdfunding platforms that facilitate online donation activities through mobile-based systems. In this context, interface usability and user experience play important roles in influencing user trust, emotional engagement, and continuity of platform usage. As one of the largest crowdfunding platforms in Indonesia, Kitabisa.com requires an interface capable of supporting effective interaction, visual clarity, and positive user experiences. This study aims to evaluate the User Interface (UI) and User Experience (UX) quality of the Kitabisa.com application using the System Usability Scale (SUS) and User Experience Questionnaire (UEQ) methods. The research employed a descriptive quantitative approach involving 30 respondents who had previously used the application for donation activities or campaign exploration. Data were collected through online questionnaires consisting of SUS and UEQ instruments. The SUS analysis produced a score of 78.0, indicating that the application falls within the acceptable usability category with good interaction quality. Furthermore, the UEQ evaluation demonstrated positive results across all dimensions, including attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The findings indicate that the application successfully supports usability efficiency, navigation clarity, and positive emotional engagement during digital donation activities. However, the novelty dimension obtained the lowest score, indicating opportunities for further innovation in interface design and interactive engagement features. This study contributes to usability evaluation research within digital crowdfunding platforms and provides recommendations for improving interface quality and user interaction experiences.